Analysis of Contractual Based Construction Implementation and Self-Managed Construction Implementation Based on Community Empowerment - Suprapto, Aki’; Wulandari, Esti; Tjendani, Hanie Teki (International Journal of Social Science and Community Service, 2024)
This research aims to determine community empowerment-based self-management construction projects and contractual-based construction projects in Sumenep District, using the AHP (Analytical Hierachy Process) method. The AHP method is used to analyze the results of the questionnaire so that the weight value of the criteria and sub criteria can be known as the basis for selecting the implementation of construction activities. Based on the results of the analysis of alternative construction implementation contractual weight is 0.501 and community empowerment is 0.499. The implementation of contractual-based construction projects is preferred with consideration of a more organized implementation, both in time (time schedule) and regulations governing it such as sanctions and fines when there are obstacles in the field being part of the responsibility for the implementation of contractual-based construction. Contractual-based construction implementation tends to be more organized and in accordance with strict schedules and regulations, including sanctions and fines if there are obstacles in the field. In contrast, self-managed construction based on community empowerment, such as in the village fund program, often has leeway in terms of a longer implementation period and supervision carried out by the community itself, not by experts. Thus, stakeholders are expected to clarify the regulations governing which works are carried out in a self-managed manner and which works are carried out contractually in government programs.